Civil wars in Africa roots and resolution - Ali, Taisier Mohamed Ahmed (Montreal McGill-Queen's University Press, 1999)
A collection of case studies of nine African countries, "Civil Wars in Africa" provides a comparative perspective on the causes of civil war and the processes by which internal conflict may be resolved or averted. The book focuses on the wars in Ethiopia, Liberia, Mozambique, Rwanda, Somalia, Sudan, and Uganda as well as the experiences of Tanzania and Zimbabwe, where civil war was averted, to underline conditions under which conflict can most successfully be managed. John Kiyaga-Nsubuga focuses on Yoweri Museveni and his National Resistance Movement regime's attempt to bring peace to Uganda. John Prendergast and Mark Duffield look at Ethiopia's long civil war and the role of liberation politics and external engagement. Bruce Jones studies the ethnic roots of the civil war in Rwanda. Elwood Dunn explores political manipulation and ethnic differences as causes of civil strife in Liberia. John Saul examines the role of Western powers in establishing peace in Mozambique. Hussein Adam describes the collapse of the authoritarian regime in Somalia and the subsequent rise of inter-clan and sub-clan rivalry. Taisier Ali and Robert Matthews argue that the forty-year conflict in Sudan is much more complex than the usual view that it results from the pitting of the Arab, Islamic North against the African, Christian South. Shifting the focus to how internal unrest may be managed, Hevina Dashwood examines government initiatives undertaken to maintain stability in Zimbabwe and Cranford Pratt describes the policies and institutions developed by Nyerere that enabled Tanzania to avoid ethnic, regional, and religious factionalism and intra-elite rivalries. James Busumtwi-Sam explores multilateral third-party intervention, highlighting the changing role of the OAU and the United Nations and their effectiveness in averting war. The concluding chapter draws together findings from the individual case studies and incorporates them into the larger corpus of the literature. Taisier M. Ali, formerly professor of political economy at the University of Khartoum, is presently a visiting scholar in the Department of Political Science, University of Toronto. Robert O. Matthews is professor of political science, University of Toronto.
Includes bibliographical references and index.
Keywords: Political violence--Africa, Sub-Saharan--History--20th century